Mutagenesis and Identification of Sugarcane Mutants Using Survival on Polyethylene Glycol and Leaf Damage under Managed Water Stress - Napa Weksanthia; Tanapon Chaisan; Wannasiri Wannarat; Songyos Chotchutima; Peeranuch Jompuk (International Journal of Agronomy)
Drought causes severe damage to sugarcane, reducing its product yield. Given Thailand’s weather conditions and topography, a breeding program to develop new sugarcane genotypes with a high tolerance for water stress is important to the sugarcane industry. This study created new water stress tolerant sugarcane genotypes using ethyl methanesulfonate (EMS) mutagenesis in the sugarcane cultivar Khon Kaen 3. Using 16 mM of EMS for 4 h induced callus mutagenesis (survival rate, 57.5%). The survival rates of calli treated with 10 mM of EMS for 2 and 4 h in selective media with 15% PEG were higher than that of non-EMS-treated calli. The selected calli survived and grew on selective media with 20% PEG, while non-EMS-treated calli did not grow. The mutant plantlets developed from EMS-treated calli on selective media with 20% PEG for 4 weeks had varying survival rates: 72.25% (10 mM of EMS for 2 h), 75.85% (10 mM of EMS for 4 h), and 60.61% (16 mM of EMS for 4 h). Both healthy mutant sugarcane plants (2,086) and non-mutant plants (234) were cultured on the media with 20% PEG for 16 weeks. Of these, 462 mutant sugarcane plantlets survived and developed on the media, but all the non-mutant sugarcane plantlets died during the selection process. Mutagenesis induced using treatment 4 produced the highest frequency of mutant sugarcane plantlets with water-stress tolerance (45.5%). In total, 136 selected mutant sugarcane plants were transplanted to a greenhouse for evaluation under managed water stress. Fourteen mutant sugarcane plants stayed green after the third cycle of water stress, but the KK3 sugarcane cultivar showed damage on 50% of the leaves. Thus, EMS mutagenesis and evaluation using in vitro and greenhouse methods were successful in developing new sugarcane clones with high water-stress tolerance, which is important for sugarcane breeding programs.